2009
DOI: 10.1007/s00520-009-0775-3
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical interventions facilitate premedication and prevent opioid-induced constipation and emesis in cancer patients

Abstract: Intervention to promote prophylactic medication was highly effective in reducing the risk of opioid-induced constipation and nausea/vomiting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…(ii) hard stools at least 25% of the time; (iii) incomplete evacuation at least 25% of the time; (iv) 2 or fewer bowel movements per week Irving et al 27 Patients were also required to have a recalled history of opioid-induced bowel dysfunction, defined as decreased BM frequency associated with opioid medication and at least 1 other BM symptom (such as hard stools or straining to pass a stool) Iyer et al 12 Constipation during the screening period was defined as <3 RFBMs per week (no laxative use within 24 h before any bowel movement) that were associated with 1 or more of the following: (a) a Bristol Stool Form Scale score (15) of 1 or 2 for at least 25% of the bowel movements; (b) straining during at least 25% of the bowel movements; (c) a sensation of incomplete evacuation after at least 25% of the bowel movements Jansen et al 28 Patients were also required to have a recalled history of opioid-induced bowel dysfunction, defined as decreased BM frequency associated with opioid medication, and at least 1 other BM symptom (such as hard stools, or straining to pass a stool) Ishihara et al 29 Constipation was defined as the lack of stools for >3 d in a week (23) Chamberlain et al 30 In addition, inclusion criteria required constipation defined as either <3 bowel movements during the preceding week, and no clinically significant bowel movement (investigator determined) within 24 h before the first study drug dose, or no clinically significant bowel movement within 48 h before the first dose Wirz et al 21 The definition of constipation is that it is a subjective symptom involving complaints of decreased stool frequency 19,31,32 but for pragmatic reasons, we defined constipation as a stool-free interval of >72 h in combination with an NRS score for constipation >4 Portenoy et al 33 Reported ongoing constipation, defined as >2 d with no bowel movement and a score of Z3 on a 5-point scale assessing constipation-related distress Webster et al 13 Opioid-induced bowel dysfunction was defined as a history of decreased bowel movement frequency since initiating opioid therapy and Z1 of the following symptoms: incomplete evacuation, hard stools, or straining, in Z25% of bowel movements Wirz et al 34 For pragmatic reasons, we defined constipation in outpatients by the detection of a stool-free interval of >72 h in combination with a NRS of constipation >4…”
Section: References Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…(ii) hard stools at least 25% of the time; (iii) incomplete evacuation at least 25% of the time; (iv) 2 or fewer bowel movements per week Irving et al 27 Patients were also required to have a recalled history of opioid-induced bowel dysfunction, defined as decreased BM frequency associated with opioid medication and at least 1 other BM symptom (such as hard stools or straining to pass a stool) Iyer et al 12 Constipation during the screening period was defined as <3 RFBMs per week (no laxative use within 24 h before any bowel movement) that were associated with 1 or more of the following: (a) a Bristol Stool Form Scale score (15) of 1 or 2 for at least 25% of the bowel movements; (b) straining during at least 25% of the bowel movements; (c) a sensation of incomplete evacuation after at least 25% of the bowel movements Jansen et al 28 Patients were also required to have a recalled history of opioid-induced bowel dysfunction, defined as decreased BM frequency associated with opioid medication, and at least 1 other BM symptom (such as hard stools, or straining to pass a stool) Ishihara et al 29 Constipation was defined as the lack of stools for >3 d in a week (23) Chamberlain et al 30 In addition, inclusion criteria required constipation defined as either <3 bowel movements during the preceding week, and no clinically significant bowel movement (investigator determined) within 24 h before the first study drug dose, or no clinically significant bowel movement within 48 h before the first dose Wirz et al 21 The definition of constipation is that it is a subjective symptom involving complaints of decreased stool frequency 19,31,32 but for pragmatic reasons, we defined constipation as a stool-free interval of >72 h in combination with an NRS score for constipation >4 Portenoy et al 33 Reported ongoing constipation, defined as >2 d with no bowel movement and a score of Z3 on a 5-point scale assessing constipation-related distress Webster et al 13 Opioid-induced bowel dysfunction was defined as a history of decreased bowel movement frequency since initiating opioid therapy and Z1 of the following symptoms: incomplete evacuation, hard stools, or straining, in Z25% of bowel movements Wirz et al 34 For pragmatic reasons, we defined constipation in outpatients by the detection of a stool-free interval of >72 h in combination with a NRS of constipation >4…”
Section: References Definitionsmentioning
confidence: 99%
“…For the majority of investigators, the objective measure stool (or bowel movement) frequency was the central element of their OIC definition. For 4 of 16 studies (25%) that provided a definition, this was the only measure used [14][15][16]29 (Supplementary Table 1, Supplemental Digital Content 2, http://links.lww.com/JCG/A165). [15][16][17][18][19][21][22][23][24][25][26] Most notably, the majority of studies that provided a definition did neither include the present or recent history of opioid therapy or functional constipation nor the change of bowel habits or defecation patterns in their definition.…”
Section: Definitionsmentioning
confidence: 99%
“…There has been little evidence indicating the efficacy of ant-emetic prophylaxis for opioid-induced nausea and vomiting. [4][5][6][7][8] Thus, a retrospective study was carried out to identify predictive factors for nausea or vomiting in patients with cancer who were given opioids for the first time, in order to be contributory to establish optimal treatment of cancer pain. January 2008 and December 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported that prophylactic antiemetics are highly effective for reducing the risk of opioid-induced nausea/vomiting. 37,38 Prophylactic medication may also be considered in patients treated with TDF. Other adverse events, including dizziness and sleepiness, were also negligible and resolved without treatment.…”
Section: Discussionmentioning
confidence: 99%